CREATION OF ACTIVE AND CREATIVE CLIMATE ON METHODICAL CLASSES FOR THE DEVELOPMENT OF CREATIVE STYLE ACTIVITIES OF TEACHER - N.V. Kovalova (Academy of Cognitive and Natural Sciences, 2003)
In the article is concretized such conception "climate", "activity" and the characteristic is given for active-creative climate, the meaning of creation ih live creative climate at the methodic lectures is reveated, the process of creating the work, the teachers results of creative group auproposed and checked.